Enhancing Security for Text Message Cryptography based on Basis Vectors - Khanal, Ramesh (Nepalese Journal of Management Research, 2024)
Cryptography is the practice and study of hiding information from all but those with the means or key to decode the message. Also the area of cryptography employs many different means of transforming normal data in to unreadable form. This paper’s aim of the study was how to keep the digital data secretly and sent it secretly through insecure channels based on basis vectors, that an activity builds around one of the techniques that illustrate an application of a set of basis vectors called matrix to cryptography The method involves two matrices of which one is used to encode the encoding matrix and the other one to decode the decoding matrix. The characters, in the original message or stream are assigned numerical values and the matrix must be row reduce echelon form for use in decoding. The proposed method is very simple in its principle and has great potential to be applied to other situations where the exchange of message is done confidentially.